Evaluation of the Therapeutic Effect of Cardamom Extract on Nephropathy Induced by Aspirin in Rats Model - AlMallah, Bayan; Al Laham, Shaza; Alkhatib , Racha; Al-Manadili, Ahmad (Jordan Journal of Pharmaceutical Sciences, 2025)
Analgesic-induced nephropathy is a serious complication resulting from the chronic overuse of analgesics, especially over-the-counter drugs such as aspirin. The study aimed to investigate the therapeutic effect of cardamom extract on aspirin-induced nephropathy in rat models. Twenty-four female Albino Wistar rats were randomly divided into three groups (n=8/group): control(no treatment); (ASA) aspirin 600 mg/kg/day for 4 days, and (ASA + Card) aspirin + cardamom extract 200 mg/kg/day for 7 days. Cardamom aqueous extract was prepared. Phenol and flavonoid contents were calculated. The kidney/body weight ratio was calculated, and serum urea and creatinine were measured. Lipid peroxidation was evaluated by measuring Malondialdehyde (MDA) concentrations, and superoxide dismutase (SOD) activity in kidney tissue. Histological alterations were also assessed. Parametric data were evaluated using the One-way analysis of variance (ANOVA) test, followed by Tukey’s test. Nonparametric data were evaluated by the Mann–Whitney test and Fisher’s tests. The results were considered significant at P<0.05. Total phenol 23.4 mg gallic acid equivalents / g dry extract, and flavonoids 1.77 mg quercetin equivalents /g dry extract. In the ASA group, kidney weight/body weight ratio, Serum biomarkers, and MDA concentrations were significantly increased, while SOD levels decreased, compared with the control group. The histological examinations showed significant tubular and glomerular injuries. There was a significant improvement in the Card histological and serum when compared with the aspirin group. Cardamom aqueous extract (200 mg/kg) showed effective therapeutic ability against aspirin-induced nephropathy by improving kidney functions, and enzymatic and histological parameters, due to their antioxidant activity in oxidative stress induced by aspirin.